Paleogene Development of Sundaland - R. P. Koesoemadinata (Berita Sedimentologi, 2026)
The Paleogene tectonostratigraphy of Sundaland can be subdivided into Pre-rift (Pre- Cenozoic and Paleocene) and Syn-rift (Eocene and Oligocene) megasequences. The Pre-rift Paleogene, represented mainly by Paleocene, was the time of non-deposition and denudation practically over the whole Sundaland, except at a few places along its peripheries, where arc volcanism took place. These volcanics are the Jatibarang and the Cikotok Volcanics in western Java, with its respective associated subduction zones at Loh Ulo and Ciletuh. In Sumatra, they are the Kikim Tuffs (South Sumatra) and the Brueh Volcanics (North Sumatra) and its associated back-arc and shelf basins (carbonate platform). At this time, the Sundaland was tectonically stable. The Syn-rift Paleogene consists of Eocene and Oligocene deposits, mainly of terrestrial facies (fluviatile and lacustrine), partly with marine incursions, such as in the North Sumatra and South Sumatra. Sedimentation was restricted to narrow rift-valleys grabens and half-grabens surrounding the core of the Sunda Shield in SW Kalimantan. The bounding faults show a definite pattern, anti-clock-wise from N Sumatra-NW Java, NW-SE and N-S; Eastern Java E-W and NNE-SSW; SE Kalimantan WNW-ESE; E. Kalimantan NNW-SSE, and Natuna basin: NE-SW and NW-SE. Tectonically, Sundaland was in an extensional regime during most of the Paleogene. In its western part, Sundaland is characterized by trans-tensional tectonics: the NW-SE trending right-lateral Mentawai Trans-current Fault (transform fault) formed a plate-boundary with corresponding Padang Island Fault forming a couple to form the N-S and NW-SE trending grabens.  In the east, the West Sulawesi micro-continent rifted away to form the Makassar Strait basins, initiating NNE-SSW trending grabens and half-grabens with syn-rift deposition. To the south, the presence of a subduction is questionable, as no volcanic rocks of either Eocene and Oligocene age has been radiometrically identified. At the continental edge, however, at least in western Java, a prograding depositional sequence of deltaic to shallow marine deposits overlain by reefal limestones have been identified similar to a passive margin depositional sequence. To the north in west central Kalimantan arc volcanism indicates the presence of fore-arc basins.